FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT UNTUK MENGGUNAKAN SISTEM KEUANGAN DESA (SISKEUDES) - Faradilla Almeyda Putri; Amy Fontanella; Desi Handayani (LP2M Politeknik Jambi, 2023)
This research aims to examine the factors that influence interest in using the Village Fund Financial System (SISKEUDES). The research method used is a survey with a quantitative approach. Respondents in this research were village officials implementing SISKEUDES. Data collection was carried out using the questionnaire method. Sampling was carried out using the saturation sampling method resulting in 52 respondents. This research uses Structural Equation Modal using Partial Least Square (PLS) as the analysis method. The research results show that partially the quality of human resources and social factors have a positive effect on interest in using SISKEUDES.